2020
DOI: 10.1007/s11239-020-02176-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and consequences of systemic arterial thrombotic events in COVID-19 patients

Abstract: A high incidence of thrombotic events, particularly deep vein thrombosis and pulmonary embolism, has been clearly documented in COVID-19 patients. In addition, small series of patients with coronary, cerebrovascular and peripheral arterial thrombotic events have also been reported, but their true incidence and consequences are not well described, and constitute the objective of this study. From February 1st to April 21st, 2020, 2115 COVID-19 patients were treated at Hospital Universitario Fundación Alcorcón (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 10 publications
3
73
2
5
Order By: Relevance
“…Ischemic Stroke 37 Articles [39], [57], [58], [60], [63], [73], [74], [75], [76] [77], [78], [79], [80],. [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [178], [192] 363 NR in all articles.…”
Section: Cerebrovascular Eventsmentioning
confidence: 96%
“…Ischemic Stroke 37 Articles [39], [57], [58], [60], [63], [73], [74], [75], [76] [77], [78], [79], [80],. [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [178], [192] 363 NR in all articles.…”
Section: Cerebrovascular Eventsmentioning
confidence: 96%
“…A thrombotic event was sometimes reported as the first presentation of COVID-19 infection ( Hughes et al, 2020 ; Klok et al, 2020 ). In a retrospective study on 214 COVID-19 patients, about 6% presented with acute cerebrovascular events, mainly ischemic strokes ( Cantador et al, 2020 ). A small number of stroke patients with COVID-19 infection presented with cerebral hemorrhage ( Cantador et al, 2020 ).…”
Section: Mechanisms Of Cns Involvementmentioning
confidence: 99%
“…In a retrospective study on 214 COVID-19 patients, about 6% presented with acute cerebrovascular events, mainly ischemic strokes ( Cantador et al, 2020 ). A small number of stroke patients with COVID-19 infection presented with cerebral hemorrhage ( Cantador et al, 2020 ). Recent investigation has also found that COVID-19 patients have increased serum Nox2 overactivation, which is an important trigger for vascular dysfunction through excess production of reactive oxygen species ( Violi et al, 2020a ).…”
Section: Mechanisms Of Cns Involvementmentioning
confidence: 99%
“…Cantador et al, in a retrospective observational study, demonstrated that out of 1419 COVID-19 patients, 14 (1%) patients developed systemic arterial thrombotic events of acute coronary syndrome, acute ischemic stroke, and acute lower limb ischemia with a mortality rate of 28.6% in these patients [10]. Similarly, a recent observational cohort study from Italy illustrated an increase in the incidence of acute limb ischemia in patients with COVID-19 from January to March 2020 compared to January to March 2019 (16.3% vs. 1.8%, respectively; p<.001) [11].…”
Section: Discussionmentioning
confidence: 99%